Bacillus sp. Effectivity test as a growth supressor agent from antrachnose disease caused by Colletotrichum sp. on cayenne pepper plant (Capsicum frutescens L.) - nita widyaningsih; Wisnu Adhi Susila; Annisa Khumaira (International Journal of Health Science and Technology, 2021)
cayenne pepper plant (Capsicum frutescens L.) is one of the popular vegetables comodity in Indonesia. cayenne pepper plant used as main ingridients for kitchen’s need, sauce industry, chili powder, instant noodle, and pharmaceutical industry. The demand for cayenne pepper plant in Indonesia is considerably high, about 4kg/capita/year. Antrachnose diseease caused by Colletotrichum sp is on of the major problem in cayenne pepper plant cultivation. Colletotrichum sp is from Nectrioidaceae family that has plenty of aservulus beneath the cuticule or on the surface, the diameter is up to 10 nm, black colored and many setae. Several bacteria has antagonist feature either around the root, or endophytes with the roots. Bacillus sp has antagonist feature is consider to treat the Antrachnose disease. Bacillus sp is a marine bactreia that can produce antibiotic to fight pathogen. However, from this study there are two different antagonist activites between two isolate due to different chytinolytic activitiy between the two isolate.